LATE GLACIAL AND HOLOCENE HISTORY OF BUXUS SEMPERVIRENS L. IN ITALY - DI DOMENICO, F.; LUCCHESE, F.; MAGRI, D. (Annali di Botanica, 2011)
In the course of the Holocene, plant species experienced changes in their area of distribution and population density in response to climate change, biotic processes and human activities. The combined use of modern and past distribution data provides a powerful tool for assessing the directions and the rates of the changes that took place. Buxus sempervirens L. (common box) is an evergreen angiosperm present in Italy with a scattered and fragmented distribution resulting from its persistence in the Peninsula through the last glacial maximum and the Holocene. Buxus experienced a progressive population growth in the course of the Holocene, with different modes and times from region to region, depending on the different densities of the starting nuclei of Buxus populations. Populations located at latitudes between 41°N and 43°N were already rather dense during the late glacial. Buxus increased in the course of the Holocene especially in N Italy, while it underwent a severe reduction in S Italy, to the point of disappearing from Sicily and Apulia. Our results demonstrate that the knowledge of Buxus history is especially important in the context of future plant distribution changes, providing a starting point for conservation action and sustainable management of biodiversity.